Abrasion phenomena of the contact tip in consumable electrode arc welding - Matsui, Hitoshi; Hattori, Taiji (Welding international, 2018)
In GMA welding, presently, fluctuation of the tip of welding wire has been able to restrain precisely, and metal transfer also has been able to regulate periodically, that is stable arc-like TIG welding has been realized. Then at this stage, reduction of contact tip abrasion is the most important subject to maintain arc stability for a long time. In this investigation, many factors are evaluated with abrasion amount, and new material of contact tip is recommended. Results obtained are as follows. Using uncoated welding wire increases contact tip abrasion rapidly as to Cu-coated welding wire. On the contrary, other welding conditions concerning contact point have almost no influence. Under the same current, the abrasion of contact tip is reduced accordingly as welding wire feeding rate becomes higher. Therefore, the abrasion is accelerated violently at the time of arc ignition because of heat accumulation at the contact point by wire stopping and high current which is needed for arc ignition. That is the welding wire which is induced to contact point with room temperature has considerable influence to cool the contact point. As a measure to reduce the abrasion at arc ignition, shortening the period of high current is effective. To cool the contact point positively, thermoelectromotive force was applied. Constantan (Cu-455Ni) has low thermoelectromotive force and high melting point than Fe. So, Cu-Ni alloy (Cu-43.3%Ni-0.92%Mn) was selected and examined as the contact tip material. The abrasion of Cu-Ni alloy contact tip becomes less than about two-tenth of the abrasion of Cu-Cr contact tip. As the conclusion, the best mixed measures which are effective to reduce the contact tip abrasion are using Cu-coated welding wire, wire retract type arc ignition and Cu-Ni alloy contact tip.